2016
DOI: 10.3329/baj.v18i2.28907
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Study on Intercropping of Hybrid Maize with Different Short Duration Vegetables in the Charland of Tangail

Abstract: An experiment was conducted in charland at the Multi Location Testing (MLT) site Bhuapur, Tangail during 2012-13 and 2013-14 under AEZ-8 to find out the suitable intercropping system of hybrid maize with different short duration vegetables with economic return. The experiment was laid out in RCB design with six dispersed (six farmers’ field) replications. The hybrid maize (ver. BARI Hybrid maize-7), potato (Diamant), spinach (local), red amaranth (BARI Lalsak-1), Radish (BARI Mula-1) were used as the planting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
4
4
0
Order By: Relevance
“…Kheroar and Patra (2013) reported that intercropping of maize and legume crops had increased the maize equivalent yield compared to sole maize. This result agrees with the findings of Mian et al (2011) and Rahaman et al (2015) where they obtained maximum maize equivalent yield in maize paired row with spinach intercropping combination. Similar results are also reported by Rana et al (2006).…”
Section: Maize Equivalent Yieldsupporting
confidence: 93%
“…Kheroar and Patra (2013) reported that intercropping of maize and legume crops had increased the maize equivalent yield compared to sole maize. This result agrees with the findings of Mian et al (2011) and Rahaman et al (2015) where they obtained maximum maize equivalent yield in maize paired row with spinach intercropping combination. Similar results are also reported by Rana et al (2006).…”
Section: Maize Equivalent Yieldsupporting
confidence: 93%
“…Similar results were observed by researchers Rahaman, et al, 2015 andHossain, et al, 2015. The lowest maize equivalent yield (9.53 t ha -1 ) was obtained from maize + red amaranth intercrop combination.…”
Section: Relative Yieldsupporting
confidence: 89%
“…Higher gross return was obtained from all intercrop combinations than sole crop. Many researchers also documented higher gross margin or net return in intercropping system than sole crop (Ali, et al, 2015;Alam et al, 2008;Bhuiyan et al, 2013;Farhad et al, 2014;Rahaman, et al, 2015 andHossain, et al, 2015). Among the combinations, the highest gross return was obtained from maize + potato intercropping system, which was 81% higher than sole maize.…”
Section: Monetary Advantagementioning
confidence: 99%
“…is is not always the case in intercropping trials between maize and other vegetables. In some cases, maize yields were reduced upon intercropping with vegetables [23,24]. us, not just the system of cultivation, but the test crop type may also affect the yield of any of the two crop species in an intercrop system.…”
Section: Intercropping Effect On Growth and Yield Attributes Of Maizementioning
confidence: 99%
“…Intercropped maize was negatively affected by intercropping with wheat, especially during its early growth for a lower leaf appearance rate [25] and a lower biomass accumulation per day [26]. Depending on the vegetable, intercropping maize with vegetables can result in higher gains as reported for intercropping hybrid maize with different short-duration vegetables [24], intercropping winter maize with vegetables [23], and intercropping maize with different vegetables [27] or no effect as shown by our study ( Table 5).…”
Section: Intercropping Effect On Growth and Yield Attributes Of Maizementioning
confidence: 99%